Мар луоз ӵуказе?: веросъёс но пьеса / Ульфат Бадретдинов - Бадретдинов Ульфат Шайхутдинович (1991)
Экземпляры: ф.2 (1992) / Инвентарный номер: 34832 / Сис.шифр: 84(2Рос=Удм)6 / Авт.знак: Б 15 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Удм)6